The Impact of Juvenile Justice Reforms in India - Kethineni, Sesha (International journal of offender therapy and comparative criminology, 2000)
This article examines changes in the juvenile justice system after passage of the comprehensive Juvenile Justice Act (1986) and the impact those changes have had on juvenile offenders in India. Specifically, this study examines how changes in the juvenile justice system impacted the types of cases brought before the juvenile courts and the types of dispositions imposed on delinquent children. Data were collected from court records in the Southern state of Tamil Nadu, India, from January 1983 to November 1997